Call the midwife. Season fifteen [videorecording (DVD)] - Thomas, Heidi, 1962- (BBC, 2026)
Uncertainty surrounds the future of Nonnatus House, with the team of midwives navigating shifting expectations in a rapidly modernising world. The midwives encounter the Women's Liberation Movement, complex medical cases such as premature birth, placenta previa, kidney cancer, tuberculosis, and even the lingering scars of slavery.